Transformación de leucoplasia verrugosa proliferativa en carcinoma oral: diez años de seguimiento - Navarro, Cláudia Maria [UNESP]; Sposto, Maria Regina; Sgavioli Massucato, Elaine Maria; Aparecida Onofre, Mirian (My University, 2004)
The authors present a case of proliferative verrucous leukoplakia (PVL) in a 78-year-old man. It was initially presented as leukoplakia on the tongue but a microscopic investigation in 1991 revealed it to be a mild epithelial dysplasia. After 5 years of follow-up, the lesion presented changes in size and location, and a recidivant behavior. In 1996, a red granular and indurated area that appeared on the tongue was found to be a microinvasive squamous cell carcinoma when microscopically investigated. After a review of the clinicopathologic behavior of this entity, the authors concluded that it was a typical PVL, whose diagnosis is difficult and retrospective, as indicated by others. The authors emphasize the importance of periodic detailed clinical and histological examination of this type of lesions in order to detect early signs of malignancy.
Transformation of proliferative verrucous leukoplakia to oral carcinoma: a ten years follow-up
Keywords: Dysplasia; Epithelial hyperplasia; Papillomatosis; Proliferative verrucous leukoplakia; Squamous cell carcinoma; aged; case report; clinical examination; dysplasia; epithelium hyperplasia; follow up; histology; human; leukoplakia; male; malignant transformation; mouth carcinoma; papillomatosis; proliferative verrucous leukoplakia; review; squamous cell carcinoma; Aged; Carcinoma, Squamous Cell; Cell Transformation, Neoplastic; Follow-Up Studies; Humans; Leukoplakia, Oral; Male; Mouth Neoplasms; Time Factors